Case report: Ewing sarcoma with EWSR–ERG fusion elevates procalcitonin extremely in the long term without infection - Chen, Ying; Qin, Tao; Chen, Yan; Gao, Ming (Frontiers in Oncology, 2023)
Background Ewing sarcoma (ES) represents a rare, aggressive bone and soft-tissue cancer. Unlike breast, liver, pancreatic, and prostate cancers, Ewing sarcoma has had no representative tumor marker until now. The use of procalcitonin (PCT) as a tumor marker is also rarely reported. PCT is a clinically recognized and widely used inflammatory marker in recent years. In rare cases, PCT may also be falsely positive due to non-infectious factors. In the few previously reported papers regarding the correlation between tumors and PCT, we learned that abnormalities of PCT level can also be impacted by individual cancers. Case presentation Here, we first reported a case of Ewing sarcoma with markedly elevated PCT without infection and carried out some literature review. The patient was a middle-aged man with extraskeletal Ewing sarcoma whose lesion was located in the distal abdominal ileum. He had a sudden and unprovoked onset of high fever during chemotherapy before surgery. After multiple examinations, the patient's blood routine, C-reactive protein, blood culture, and CT examination showed no signs of infection, and even the culture from the end of the central venous catheter showed no pathogen growth. Only PCT increased dramatically to more than 200ng/ml. PCT remained at this level for several months until a single abdominal lumpectomy was performed before it dropped to near-normal levels. Conclusion In our report, PCT is significantly elevated in Ewing's sarcoma in the absence of infection. Not only that, but we particularly highlighted the precipitous drop in PCT following tumor resection.